Penggambaran Terorisme Dalam Film “Sayap - Sayap Patah” - Prayoga, Adrian Bima; Suratnoaji, Catur (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Film has become a familiar audio-visual communication medium enjoyed by people of all ages and social backgrounds. The film Sayap - Sayap Patah, which recently appeared on Indonesian film screens, has become a public concern and is trending on Twitter social media. This is because the story behind it tells about the terrorist atrocities that occurred in the film. Apart from that, the film shows the scene of the main terrorist mastermind to invite his colleagues to carry out their duties under the pretext of religious interests under the guise of politics. The purpose of this study is to explain the representation of terrorism in the film Sayap-Sayap Patah using semiotic analysis. This study uses descriptive qualitative approach with Roland Barthes semiotics to find out the depiction or representation of terrorism that occurs in the film sayap – sayap patah. The results of the research that can be taken are in this film that there are scenes that contain symbols and signs regarding representations depicting acts of terrorism both through scenes and dialogues which are analyzed using the semiotics of Roland Barthes' perspective, namely emphasizing the system of meaning of signs or symbols used in a film goes through two stages, namely the meaning of denotation and connotation where in the second stage, namely connotation, the sign works through myth (myth). Keywords: semiotics, film, terrorism